Research on Human Resource Development in the Xinhui Tangerine Peel Industry: Current Status, Challenges, and Countermeasures (Journal of economic and management development research, 2026)
Under the deepening implementation of the rural revitalization strategy, the Xinhui Tangerine Peel industry, as a key modern agricultural cluster prioritized under Guangdong Province’s "Hundred-Thousand-Myriad Project," has evolved from a traditional single sun-drying processing model to a billion-yuan-level modern industrial cluster integrating planting, processing, R&D, cultural tourism, and e-commerce. However, with the accelerating transition toward high-quality development, the industry faces core challenges in human resource development, including structural talent shortages, mismatches between workforce competencies and industrial demands, and inadequate mechanisms for talent cultivation, safeguarding, and incentives. Existing research primarily focuses on the industry’s developmental trajectory, branding strategies, and market analysis, lacking systematic exploration of its human resource status, structural characteristics, and optimization strategies. This study systematically analyzes the current human resource landscape of the Xinhui Tangerine Peel industry, synthesizes insights from industrial practices and existing research, and proposes feasible optimization strategies across three dimensions: talent recruitment and workforce allocation, improvement of talent training systems, and refinement of safeguard and incentive mechanisms. The findings aim to provide practical support for resolving talent bottlenecks and achieving the industry’s leap from a billion-yuan to a trillion-yuan industrial cluster, while also offering actionable references and theoretical insights for optimizing human resource management in China’s specialty agricultural industries and advancing rural revitalization through talent-driven strategies.
Keywords: Xinhui tangerine peel; Human resources; Talent structure; Rural revitalization; Industrial chain; Talent cultivation; Industrial optimization and upgrading; Talent incentive mechanisms; School-Enterprise collaboration; New-Generation agricultural professionals; Agricultural products